Impact of brick-kiln industry on the surrounding natural environment in the Asansol city of West Bengal - Suvra Maji; Sarfaraz Alam (National Geographical Journal of India, 2025)
The rising demand for bricks in India’s urban construction sector has led to the widespread proliferation of brick kilns in the peripheral zones of cities. In Asansol, this phenomenon is particularly evident, with fifteen brick kilns concentrated across eight outer municipal wards, occupying over 70 hectares of land. This study investigates the environmental implications of brick kiln operations in the peripheral areas of Asansol city, emphasizing local residents’ perceptions of the resultant land-use changes and ecological degradation. Drawing on data collected from 100 respondents residing in proximity to four selected brick kilns, the research captures diverse perspectives, including those of kiln owners, land lessors, local inhabitants, and shopkeepers. The findings reveal that brick kiln activities have significantly altered the physical landscape and contributed to the degradation of various components of the biophysical environment, including water bodies, groundwater levels, vegetation cover, soil quality, agricultural land, and cropping patterns. The study underscores the urgent need for regulatory mechanism and sustainable land-use planning to mitigate the adverse environmental impacts associated with unregulated brick kiln expansion in urban fringe areas.